Flexible Triangle Search Algorithm for Block-Based Motion Estimation. (2nd October 2006) - Rehan Rehan, Mohamed Mohamed; Agathoklis Agathoklis, Pan Pan; Antoniou Antoniou, Andreas Andreas
Abstract : A new fast algorithm for block-based motion estimation, the flexible triangle search (FTS) algorithm, is presented. The algorithm is based on the simplex method of optimization adapted to an integer grid. The proposed algorithm is highly flexible due to its ability to quickly change its search direction and to move towards the target of the search criterion. It is also capable of increasing or decreasing its search step size to allow coarser or finer search. Unlike other fast search algorithms, the FTS can escape from inferior local minima and thus converge to better solutions. The FTS was implemented as part of the H.264 encoder and was compared with several other block matching algorithms. The results obtained show that the FTS can reduce the number of block matching comparisons by around 30–60% with negligible effect on the image quality and compression ratio.